Discovery of two neighbouring satellites in the Carina constellation with MagLiteS - Torrealba, Gabriel; Martin, Nicolas F.; Martínez-Delgado, David; Noël, Noelia E. D. (Monthly notices of the Royal Astronomical Society, 2018)
We report the discovery of two ultra-faint satellites in the vicinity of the Large Magellanic Cloud (LMC) in data from the Magellanic Satellites Survey (MagLiteS ). Situated 18 deg (∼20 kpc) from the LMC and separated from each other by only 18 arcmin, Carina II and III form an intriguing pair. By simultaneously modelling the spatial and the colour-magnitude stellar distributions, we find that both Carina II and Carina III are likely dwarf galaxies, although this is less clear for Carina III. There are in fact several obvious differences between the two satellites. While both are well described by an old and metal poor population, Carina II is located at ∼36 kpc from the Sun, with MV ∼ −4.5 and rh ∼ 90 pc, and it is further confirmed by the discovery of 3 RR Lyrae at the right distance. In contrast, Carina III is much more elongated, measured to be fainter (MV ∼ −2.4), significantly more compact (rh ∼ 30 pc), and closer to the Sun, at ∼28 kpc, placing it only 8 kpc away from Car II. Together with several other systems detected by the Dark Energy Camera, Carina II and III form a strongly anisotropic cloud of satellites in the vicinity of the Magellanic Clouds.
Gesehen am 14.03.2018